(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Interstitial pregnancy occurs when the fertilised ovum implants in the interstitial portion of the fallopian tube. It occurs in around 2% of all the ectopic pregnancies . It can last up to mid trimester before it ruptures spontaneously as it can grow inside the interstitium for long period of time. If not detected early, can lead to a fatal outcome. Mifepristone (antiprogesterone) followed by a low dose of misoprostol (prostaglandin E1 analog) has been used for termination of early pregnancy after ruling out ectopic pregnancy, but there have been many reports of misuse of this combination especially in the developing countries. Here we report a case of interstitial pregnancy, which ruptured at 6 weeks of gestation due to misuse of this combination as an over the counter drug without looking for ectopic pregnancy. Bangladesh J Obstet Gynaecol, 2013; Vol. 28(2) : 103-105